Identification of differential microRNA expression during tooth morphogenesis in the heterodont dentition of miniature pigs, SusScrofa. Issue 1 (December 2015) - Li, Ang; Li, Ye; Song, Tieli; Wang, Fu; Liu, Dayong; Fan, Zhipeng; Cheng, San; Zhang, Chunmei; Wang, Jinsong; He, Junqi; Wang, Songlin
Abstract Background It has been found that microRNAs (miRNAs) play important roles in the regulation of tooth development, and most likely increase the complexity of the genetic network, thus lead to greater complexity of teeth. But there has been no research about the key microRNAs associated with tooth morphogenesis based on miRNAs expression profiles. Compared to mice, the pig model has plentiful types of teeth, which is similar with the human dental pattern. Therefore, we used miniature pigs as large-animal models to investigate differentially expressed miRNAs expression during tooth morphogenesis in the early developmental stages of tooth germ. Results A custom-designed miRNA microarray with 742 miRNA gene probes was used to analyze the expression profiles of four types of teeth at three stages of tooth development. Of the 591 detectable miRNA transcripts, 212 miRNAs were continuously expressed in all types of tooth germ, but the numbers of miRNA transcript among the four different types of teeth at each embryonic stage were statistically significant differences (p  < 0.01). The hierarchical clustering and principal component analysis results suggest that the miRNA expression was globally altered by types and temporal changes. By clustering analysis, we predicted 11 unique miRNA sequences that belong to mir-103 and mir-107, mir-133a and mir-133b, and mir-127 isomiR families. The results of real-time reverse-transcriptase PCR andin situ hybridization experiments revealed that five representative miRNAs may play important roles during different developmental stages of the incisor, canine, biscuspid, and molar, respectively. Conclusions The present study indicated that these five miRNAs, including ssc-miR-103 and ssc-miR-107, ssc-miR-133a and ssc-miR-133b, and ssc-miR-127, may play key regulatory roles in different types of teeth during different stages and thus may play critical roles in tooth morphogenesis during early development in miniature pigs.